Illocution Speech in Sociology Learning Videos on the Pahamify Channel Playlist - Riska Rahmawati; Mega Ananda Pratiwi; Efra Elya; Vivia Rahmawati; Siti Hajizah; Siska Rakhmawati (Universitas Negeri Semarang, 2025)
Developments in information technology have increased access to educational videos, including those on sociology broadcast on the Pahamify Channel. The effectiveness of video communication is primarily determined by the use of illocutionary acts, which can convey more profound meaning and encourage viewers. This study aims to identify and describe the types and forms of illocutionary acts found in sociological educational videos on the Pahamify Channel playlist, and to analyze their contribution to strengthening understanding of the material. In conducting this research, the author used a descriptive qualitative methodological approach. Data collection using this method involved observation and note-taking. This study used speech analysis techniques and a descriptive qualitative analysis approach. Based on the analysis of the sociology learning videos in the Pahamify channel playlist, 9 assertive illocutionary acts, 4 directive illocutionary acts, 1 expressive act, and 1 commissive act were identified, with no declarative illocutionary acts. In addition to serving as a reference for analyzing illocutionary acts, this study also enriches the study of speech acts in educational videos, especially in mathematics.